Prevalence of age-related macular degeneration and retinal pseudodrusen in an elderly population: the ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Fakhretdinova, Albina A.; Gilmanshin, Timur R.; Panda-Jonas, Songhomitra; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2024)
To assess the prevalence of age-related macular degeneration (AMD) and reticular pseudodrusen (RPD) in very old individuals.
Gesehen am 14.05.2025